1998
DOI: 10.2307/1170753
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Discovery Learning with Computer Simulations of Conceptual Domains

Abstract: Scientific discovery learning is a highly self-directed and constructivistic form of learning. A computer simulation is a type of computer-based environment that is very suited for discovery learning, the main task of the learner being to infer, through experimentation, characteristics of the model underlying the simulation. In this article we give a review of the observed effectiveness and efficiency of discovery learning in simulation environments together with problems that learners may encounter in discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
359
1
35

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(403 citation statements)
references
References 29 publications
8
359
1
35
Order By: Relevance
“…In the sciences students can be given questions in which they need to form testable hypotheses, and then plan and execute an experiment (de Jong & van Jooligen, 1998). In statistics, simulation provides one of the means by which an experiment can be carried out.…”
Section: Discovery Learning and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sciences students can be given questions in which they need to form testable hypotheses, and then plan and execute an experiment (de Jong & van Jooligen, 1998). In statistics, simulation provides one of the means by which an experiment can be carried out.…”
Section: Discovery Learning and Simulationmentioning
confidence: 99%
“…Students are not always proficient in noticing regularities in the data and may also be poor at interpreting graphs. Because students may be resistant to conceptual change, they may not be able to adapt hypotheses even when the data are contradictory (de Jong & van Jooligen, 1998). In statistics education, it has also been found that students can apparently be successful in their use of the computer simulation software yet still demonstrate a lack of understanding and hold misconceptions afterwards (delMas, Garfield, & Chance, 1999).…”
Section: Discovery Learning and Simulationmentioning
confidence: 99%
“…Unguided inquiry learning has been criticized as ineffective and cognitively too challenging for learners (Alfieri et al, 2011;Kirschner, Sweller, & Clark, 2006;Mayer, 2004). In inquiry-based learning, learners may have issues with generating suitable hypotheses, with designing experiments, and with drawing conclusions and/or regulating their own learning process (de Jong & van Joolingen, 1998;de Jong & Lazonder, 2014). These issues may be exacerbated by the use of simulations instead of physical, hands-on experiments.…”
Section: Guidance For Inquiry-based Learningmentioning
confidence: 99%
“…The history of simulation studies offers knowledge that may be helpful in designing learning games (for a history of simulations, see De Jong & van Joolingen, 1998). For example, one key challenge when using simulations has been how to generate an in-depth understanding of content (De Jong, 2006), as improved visualizations do not necessarily translate into better learning.…”
Section: Introductionmentioning
confidence: 99%